2012
DOI: 10.1080/19440049.2011.649304
|View full text |Cite
|
Sign up to set email alerts
|

Time‐ and temperature‐dependent migration studies of Irganox 1076 from plastics into foods and food simulants

Abstract: The study provides an exhaustive set of migration data for octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (Irganox 1076) from low-density polyethylene (LDPE) in several food matrices. Irganox 1076 was used as a model migrant because it represents one of the typical substances used as an antioxidant in food packaging polymers. Kinetic (time-dependent) migration studies of Irganox 1076 were performed for selected foodstuffs chosen with different physical-chemical properties and in relation to the actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…The negative effects of these migrants to food safety can no longer be over looked if safety of the food supply is to be assured [79]. Chemical migrants from polyethylene in both simulants and true foods have been reported in Europe, being high in oily foods under higher temperature [80] [81]. Similar trends have been reported in Brazil [82].…”
Section: Migrants From Packaging Materialssupporting
confidence: 65%
“…The negative effects of these migrants to food safety can no longer be over looked if safety of the food supply is to be assured [79]. Chemical migrants from polyethylene in both simulants and true foods have been reported in Europe, being high in oily foods under higher temperature [80] [81]. Similar trends have been reported in Brazil [82].…”
Section: Migrants From Packaging Materialssupporting
confidence: 65%
“…Quantification and the SML of antioxidants are also of interest because these compounds and their degradation products migrate from plastics into food during processing and storage (Gao and others ). Several studies have quantified the migration of antioxidants and their degraded product from different polymers under various conditions (Jickells and others ; Garde and others ; Dopico‐García and others ; Alin and Hakkarainen , ; Gao and others ; Beldi and others ; Reinas and others ). Antioxidant migration has been widely studied in PP and polyolefins (LDPE) (Goydan and others ; Jeon and others ; Beldi and others ).…”
Section: Chemical Compound Migration Into Food and Food‐simulating LImentioning
confidence: 99%
“…Several studies have quantified the migration of antioxidants and their degraded product from different polymers under various conditions (Jickells and others ; Garde and others ; Dopico‐García and others ; Alin and Hakkarainen , ; Gao and others ; Beldi and others ; Reinas and others ). Antioxidant migration has been widely studied in PP and polyolefins (LDPE) (Goydan and others ; Jeon and others ; Beldi and others ). Garde and others () characterized the migration of antioxidants from PP films of different thicknesses into n ‐heptane and 95% ethanol at 20, 37 and 60 °C, and found that the swelling of polymer in n ‐heptane greatly increased migration rates compared to ethanol.…”
Section: Chemical Compound Migration Into Food and Food‐simulating LImentioning
confidence: 99%
See 2 more Smart Citations